Evaluation Of Ex-Ante Digital Nomad Island Policy (Case Study In The Thousand Islands (Kepulauan Seribu), Dki Jakarta Province) - Alyani, Chitra (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The development of information and communication technology has transformed work paradigms globally, driving the emergence of the digital nomad phenomenon. Digital nomads represent a new lifestyle that allows individuals to work independently and flexibly, without being tied to a specific geographical location. They utilize digital technology to conduct their work from various locations around the world, creating a dynamic and diverse global community. In response to this trend, governments and policymakers have begun to consider regulations or policies that support the presence of digital nomads within their jurisdictions. For instance, the DKI Jakarta provincial government proposed the Thousand Islands (Kepulauan Seribu) as a Digital Nomad Island during the COVID-19 pandemic in 2020. However, it is crucial to evaluate the effectiveness and consequences of such policies before implementation. Evaluating digital nomad policies is an important step in the policy formulation process, as it allows policymakers to understand the potential impacts of these policies prior to their execution. Nonetheless, empirical research focusing on the evaluation of digital nomad policies remains limited in academic literature. This study employs a qualitative approach, utilizing field observations and in-depth interviews, which are then analyzed using data reduction methods, conclusion drawing, and narrative data presentation. The findings indicate that the government's initial steps in planning the islands as a digital nomad destination have shown positive potential, with considerable community support observed. However, the evaluation also highlights several areas needing improvement in policy implementation, such as infrastructure, public services, and supporting facilities for digital nomads. Additionally, the importance of ensuring a balance between enhancing attractiveness for digital nomads and maintaining environmental sustainability and local community welfare is emphasized in the evaluation.